2022
DOI: 10.1186/s12893-022-01797-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical outcomes among open, laparoscopic, and robotic pancreatoduodenectomy: a single-center retrospective study

Abstract: Background There is no general consensus on the feasibility and safety of robotic pancreatoduodenectomy (RPD) and whether it increases surgical risks. The purpose of this study was to assess the safety, feasibility, and rationality of RPD by comparing perioperative data among open pancreatoduodenectomy (OPD), laparoscopic pancreatoduodenectomy (LPD), and RPD performed in our center in recent years. Methods Clinical data of patients had undergone RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Some studies have shown that prolonging the operation time will increase the perioperative complications and mortality of PD. 8 Prolonged operation time often means increased possibility of intraoperative bleeding and blood transfusion.…”
Section: An Assessment Of Perioperative Outcomes For Open Laparoscopi...mentioning
confidence: 99%
“…Some studies have shown that prolonging the operation time will increase the perioperative complications and mortality of PD. 8 Prolonged operation time often means increased possibility of intraoperative bleeding and blood transfusion.…”
Section: An Assessment Of Perioperative Outcomes For Open Laparoscopi...mentioning
confidence: 99%
“…6,7 Compared with open pancreaticoduodenectomy (OPD), RPD is more feasible to perform complex surgery with the advantage of three-dimensional binocular vision and high degrees of freedom. [8][9][10] And with modified ergonomics and elevated dexterity, RPD reduces surgeon fatigue and allows for greater performance of the surgeon's skills. 11,12 RPD is considered to have many advantages over OPD, such as lower blood loss, reduced perioperative complications, faster postoperative recovery, and comparable oncology outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] RPD is rapidly developing in China, although it has not yet been commonly adopted due to the high cost of instruments and the inexperience of the surgeon. 9,13 The postoperative healthcare-associated infections (HAIs), as one of the common postoperative complications of PD, have a profound impact on the prognosis of patients and the cost of medical care and increase the risk of mortality. [17][18][19] Owing to the presence of a learning curve and the complexity of the surgery, 16,20 RPD is no exception to the risk of postoperative HAIs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations